HUBUNGAN MOTIVASI, HARAPAN, DAN DUKUNGAN PETUGAS KESEHATAN TERHADAP KEPATUHAN PASIEN GAGAL GINJAL KRONIK UNTUK MENJALANI HEMODIALISIS - Rahma ' Dani; Gamya Tri Utami; Bayhakki ' ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract This research aimed to determine the relationship between motivation, expectation, and support of health care provider with adherence of chronic renal failure patients undergoing hemodialysis. The research used descriptive correlation design with cross sectional approach. The research was conducted in Hemodialysis unit at Arifin Achmad Hospital with 72 samples and chosen by purposive sampling technique with selected base inclusion criteria. Instrument used in the study was questionnaires that on validity and reliability test. The univariate analysis was conducted to show frequencies distribution and bivariate analysis was conducted by using Chi-Square. The results showed that there was correlation between motivation with adherence of chronic renal failure patients undergoing hemodialysis with p value (0,004), there was correlation between expectation with adherence of chronic renal failure patients undergoing hemodialysis with p value (0,000), and there was correlation between support of health care provider with adherence of chronic renal failure patients undergoing hemodialysis with p value (0,004) < α (0,05). The result of this study recommend health care provider in Hemodialisys unit to give support and health education continuously about adherence to increase patient’s adherence for undergoing hemodialysis. Keywords: Adherence, expectation, support of health care provider, hemodialysis, motivation